Brain function - not size - is important - Taskapilioglu, Ozlem; Taskapilioglu, M. Ozgur; Hakyemez, Bahattin; Bekar, Ahmet (The European Research Journal, 2017)
Some incidental findings on cranial imaging may render every one speechless. Brain plasticity in childhood and slow expansion of arachnoid cyst may be possible explanations of the discordance between the clinical and radiological findings. Here, we presented an asymptomatic, incidentally detected arachnoid cyst accompanied by compression of most parts of brain, displacing the motor cortex to the occipital parts of the existing brain tissue. The case was discussed in the light of the rare patients in the literature.